Experimental and numerical investigation of the thermal performance of evaporative cooled greenhouses in hot and arid climates. (7th February 2020) - Ghani, Saud; El-Bialy, Esmail Mohamed Ali Ahmed; Bakochristou, Foteini; Mohamed Rashwan, Mohammed; Mohamed Abdelhalim, Ayman; Mohammad Ismail, Salman; Ben, Pratheesh
Abstract : The controlled microclimate of greenhouses is vital for producing quality yield. This paper investigates the thermal performance of an evaporative cooled greenhouse operating in Qatar. Three design factors affecting the greenhouse thermal performance were assessed, namely the greenhouse geometry, operational parameters, and its geographical location. Geometrical parameters include induction fan elevation, roof shape, and aspect ratio. Operational parameters refer to the air flowrate. The greenhouse location dictates the incident solar intensity that was studied. Computational Fluid Dynamics (CFD) was used to model a typical ASHRAE compliant greenhouse. The simulation results were validated using measured data of a greenhouse inner air temperature, relative humidity, and the global incident solar radiation, showing good agreement. Simulation results showed that induction fans located at or below the crop height resulted in lowering the average temperature of the greenhouse. Doubling of the greenhouse ventilation rate from 20 ACH to 40 ACH further decreased the greenhouse air temperature. Temperature rise due to high incident solar radiation is reduced by increasing the ventilation rates. The uneven span greenhouse roof shape resulted in the lowest average inner temperature. For the same greenhouse floor area and volume, the effect of the aspect ratio showed negligible differences.